CoS2 / MoS2 composite material and synthesis method thereof
By combining solvent-thermal method, room temperature stirring method and hydrothermal vulcanization method, CoS2/MoS2 composite material was prepared, which solved the problem of limited application of the material in the prior art, and achieved precise control of the micromorphology of the material and Possibility of mass production.
Patent Information
- Application Number
- CN202411408575.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-21
AI Technical Summary
There are fewer reports on the preparation of CoS2/MoS2 composite materials in the prior art, which limits the exploration and development of the application of this material in a wider field.
CoS2/MoS2 composite materials are prepared by combining solvent-thermal method, room temperature stirring method and hydrothermal vulcanization method. By constructing a unique reaction system and controlling the crystal growth kinetics process, the phase composition of the CoS2/MoS2 rod-shaped structure is accurately controlled and the phase composition of the CoS2/MoS2 rod-shaped structure is Its microscopic form.
It realizes precise regulation of the phase composition and micromorphology of CoS2/MoS2 composite materials, which has far-reaching scientific theoretical value and significant practical application significance, and is suitable for large-scale production.
Smart Images

Figure CN119488925A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional inorganic material preparation, and further to a CoS2 / MoS2 composite material and a synthesis method thereof. Background Art
[0002] Molybdenum and its compounds are widely used in catalysts, alkaloid reagents, enamel ceramic glaze pigments and drugs. They can also be used in solid batteries, gas sensors, lubricants, preservatives and fungicides, etc. Moreover, molybdenum-based materials have low toxicity and are beneficial to human health and environmental protection. Among them, MoO3 is an important chemical raw material. MoO3 has excellent photochromic and electrochromic properties and can be used as optical and electrical device materials. It has been widely used in building lighting control systems and reflectivity-adjustable surfaces. MoO3 films and powders also have important applications in photocatalysis and gas sensors.
[0003] MoO3 is an n-type semiconductor oxide (Eg = 3.1eV). MoO3 has two common crystal structures, h-MoO3 and α-MoO3. Different synthesis methods can effectively regulate the microscopic morphology and phase structure of MoO3 products. Among them, MoO3 one-dimensional micro-nano materials have the characteristics of large specific surface area, high surface activity, and easy regulation of electron transfer process. They can be used as matrix materials with excellent physical and chemical properties in the field of gas sensing. In recent years, the research and development of MoO3-based one-dimensional composite gas-sensitive materials has become a research hotspot in this field. For example, the application number is CN201210417188.0, and the name is "Synthesis method of monodisperse molybdenum trioxide solid microspheres". Hydrogen peroxide is added to a methanol solution of acetylacetonato molybdenum oxide, and a black precursor is obtained after a solvothermal reaction. The precursor is then heat-treated at 300-400°C to obtain monodisperse molybdenum trioxide solid microspheres.
[0004] However, at present, there are relatively few literature reports on the preparation of CoS2 / MoS2 composite materials, both in the international and domestic research fields. Specifically, the research content involving the synthesis method of loading specific particles on the surface of molybdenum-based materials, process optimization and performance regulation has not yet formed a broad research hotspot, which to a certain extent limits the application exploration and development of this material in a wider range of fields. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a CoS2 / MoS2 composite material and a synthesis method thereof, and the CoS2 / MoS2 composite material is prepared by combining a solvothermal method, a room temperature stirring method and a hydrothermal vulcanization method. The CoS2 / MoS2 composite material is rod-shaped MoS2 with CoS2 particles loaded on the surface. A unique reaction system is innovatively constructed to control the crystal growth kinetics process, thereby accurately controlling the phase composition and micromorphology of the CoS2 / MoS2 rod-shaped structure. The method not only has profound scientific and theoretical value, but also has significant practical application significance. Moreover, the synthesis method has the advantages of easy parameter control, good product morphology repeatability, and high yield, and is suitable for large-scale production.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a method for synthesizing a CoS2 / MoS2 composite material, comprising: adding rod-shaped MoO3 to a mixture of methanol and propylene glycol, then adding polyvinyl pyrrolidone and a soluble cobalt salt, and mixing them evenly to obtain a solution A; adding a solution B of 2-methylimidazole and benzimidazole to the solution A, and obtaining a Co-Mo / C precursor after stirring, washing, drying and roasting; dispersing the Co-Mo / C precursor in deionized water, adding a sulfur source to carry out a hydrothermal sulfurization reaction, and finally obtaining the CoS2 / MoS2 composite material after washing, drying and roasting the product.
[0008] In some embodiments, the preparation process of the rod-shaped MoO3 is as follows: concentrated nitric acid, isopropanol and deionized water are mixed uniformly, and then H 24 Mo7N6O 24 ·4H2O is stirred evenly, and the obtained mixed solution is subjected to hydrothermal reaction, washing and drying in sequence to obtain the rod-shaped MoO3.
[0009] In some embodiments, the molar ratio of the rod-shaped MoO3, the polyvinyl pyrrolidone, the soluble cobalt salt, the 2-methylimidazole and the benzimidazole is 1: (0.5-2): (0.05-0.25): (0-1.5): (0-0.1); the molar number of the polyvinyl pyrrolidone is calculated as a monomer, and its monomer molar mass is 111; the molecular weight of the polyvinyl pyrrolidone is less than 1 million.
[0010] In some embodiments, the soluble cobalt salt is any one of cobalt nitrate, cobalt chloride, and cobalt sulfate.
[0011] In some embodiments, the stirring time of adding the solution B of 2-methylimidazole and benzimidazole into the solution A is 2 to 6 hours.
[0012] In some embodiments, the temperature of the hydrothermal vulcanization reaction is 150-240° C., the heating rate is 1-3° C. / min, and the time of the hydrothermal vulcanization reaction is 12-36 hours.
[0013] In some embodiments, the volume ratio of the concentrated nitric acid, the isopropanol and the deionized water is 1:(0.01-0.06):(2-5); the mass fraction concentration of the concentrated nitric acid is 69%; and / or the temperature of the hydrothermal reaction is 160-220° C., and the time of the hydrothermal reaction is 12-36 h.
[0014] The present invention also provides a CoS2 / MoS2 composite material, wherein the CoS2 / MoS2 composite material is a rod-shaped MoS2 with surface-loaded particles, and the loaded particles are CoS2; the synthesis method of the CoS2 / MoS2 composite material comprises: mixing concentrated nitric acid, isopropanol and deionized water, adding H 24 Mo7N6O 24 ·4H2O is subjected to solvent thermal reaction to obtain rod-shaped MoO3; the rod-shaped MoO3 is mixed with a mixed solution of methanol and propylene glycol, polyvinyl pyrrolidone and a soluble cobalt salt, and then 2-methylimidazole and benzimidazole are added, and the mixture is stirred evenly at room temperature, and then washed, dried and calcined to obtain Co-Mo / C; the Co-Mo / C is dispersed in deionized water, a sulfur source is added for hydrothermal vulcanization, and the obtained CoS2 / MoS2 precursor is washed, dried and calcined to obtain a CoS2 / MoS2 composite material.
[0015] In some embodiments, the diameter of the rod-shaped MoS2 is 0.1 to 1 μm, and the aspect ratio is 10 to 30:1; the particle size of the supported particles is 0.01 to 0.5 μm.
[0016] The present invention also provides an application of a CoS2 / MoS2 composite material. The CoS2 / MoS2 composite material is used in the direct synthesis of low-carbon alcohols from synthesis gas, has excellent reaction activity and low-carbon alcohol selectivity, and has good application prospects.
[0017] Compared with the prior art, the CoS2 / MoS2 composite material and the synthesis method thereof provided by the present invention have the following beneficial effects:
[0018] 1. The synthesis method of the CoS2 / MoS2 composite material provided by the present invention innovatively constructs a unique reaction system, and adopts a combination of a solvothermal method, a room temperature stirring method and a hydrothermal vulcanization method to prepare a CoS2 / MoS2 composite material that is a rod-shaped MoS2 with CoS2 particles loaded on the surface. The synthesis method introduces appropriate functional reagents, such as PVP, etc., in different reaction processes. These functional reagents optimize the microstructure of the MoO3 material and improve the stability and yield of the precursor, which is crucial for synthesizing a CoS2 / MoS2 composite material with uniform loading and good performance. In addition, different mixed solvent systems are carefully designed in the synthesis method. These solvent systems can effectively control the dissolution of the precursor, the formation of the product and the crystal growth, thereby realizing the precise regulation of the physical phase composition and micromorphology of the CoS2 / MoS2 composite material;
[0019] 2. This synthesis method has the advantage of easy control of experimental parameters. Researchers can effectively guide the reaction process to ensure that the quality and performance of the product meet the expected standards, thereby improving the accuracy of the synthesis. Moreover, the morphology of the synthesized product has good reproducibility, which provides a guarantee for the stability and reliability of the material performance. It has a large output and is suitable for large-scale production. It provides an efficient, stable and broadly applicable approach for the industrialization of CoS2 / MoS2 composite materials, which means that this synthesis method is not limited to laboratory research, but has the potential to be transformed into industrial production, which plays an important role in promoting the development of related industries and technological innovation. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The preferred implementation modes will be described below in a clear and understandable manner with reference to the accompanying drawings to further illustrate the above-mentioned characteristics, technical features, advantages and implementation methods of the present invention.
[0021] Figure 1 A flowchart of a method for synthesizing a CoS2 / MoS2 composite material provided by the present invention;
[0022] Figure 2 The X-ray powder diffraction (XRD) pattern of the rod-shaped MoO3 provided by the present invention;
[0023] Figure 3 The X-ray powder diffraction (XRD) pattern of the rod-shaped MoO3 provided by the present invention;
[0024] Figure 4 The scanning electron microscope (SEM) image of rod-shaped MoS2 with surface-loaded CoS2 particles provided by the present invention. DETAILED DESCRIPTION
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.
[0026] In order to simplify the drawings, only the parts related to the invention are schematically shown in each figure, and they do not represent the actual structure of the product. In addition, in order to simplify the drawings and facilitate understanding, in some figures, only one of the parts with the same structure or function is schematically drawn or marked. In this article, "one" not only means "only one", but also means "more than one".
[0027] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0028] In this document, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0029] In addition, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.
[0030] Example 1
[0031] The present invention provides a method for synthesizing a CoS2 / MoS2 composite material. Figure 1 The flowchart shown includes the following steps:
[0032] S3. Add rod-shaped MoO3 to a mixed solution of methanol and propylene glycol, mix evenly by ultrasonication, then add polyvinyl pyrrolidone PVP and a soluble cobalt salt, stir evenly to obtain solution A.
[0033] S4, adding the mixed solution B of 2-methylimidazole and benzimidazole to the solution A obtained in step S3.
[0034] S5. The mixed liquid obtained in step S4 is stirred, washed, dried and calcined to obtain a Co-Mo / C precursor.
[0035] S6. Disperse the Co-Mo / C precursor in deionized water, add a sulfur source, stir evenly, and perform a hydrothermal sulfurization reaction.
[0036] The products obtained by S7 and S6 are centrifugally washed, dried and calcined to obtain the above-mentioned CoS2 / MoS2 composite material.
[0037] The CoS2 / MoS2 composite material obtained by the above synthesis method is a rod-shaped MoS2 with surface-loaded particles, the loaded particles are CoS2, the diameter of the rod-shaped MoS2 is 0.1-1 μm, the aspect ratio is (10-30):1, the particle size of the CoS2 particles is 0.01-0.5 μm, Figure 4 A scanning electron microscope (SEM) image of rod-shaped MoS2 loaded with CoS2 particles is shown.
[0038] In some embodiments, in step S3 and step S4, the molar ratio of rod-shaped MoO3, polyvinyl pyrrolidone PVP, soluble cobalt salt, 2-methylimidazole and benzimidazole is 1: (0.5-2): (0.05-0.25): (0-1.5): (0-0.1).
[0039] In some embodiments, in step S3, the molar number of polyvinylpyrrolidone PVP is calculated on a monomer basis, and the molar mass of the monomer is 111.
[0040] Furthermore, the molecular weight of polyvinylpyrrolidone (PVP) is less than 1 million.
[0041] In some embodiments, in step S3, the soluble cobalt salt is any one of cobalt nitrate, cobalt chloride, and cobalt sulfate.
[0042] In some embodiments, in step S5, the stirring time after 2-methylimidazole and benzimidazole are added to the mixed solution is 2 to 6 hours.
[0043] In some embodiments, in step S6, the temperature of the hydrothermal vulcanization reaction is 150-240° C., the heating rate is 1-3° C. / min, and the time of the hydrothermal vulcanization reaction is 12-36 h.
[0044] In some embodiments, in step S6, the sulfur source is preferably thioacetyl.
[0045] In some embodiments, the present invention also provides a process for preparing rod-shaped MoO3:
[0046] S1. Mix concentrated nitric acid, isopropanol and deionized water evenly, then add H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0047] S2. The mixed solution obtained in step S1 is subjected to hydrothermal reaction, washing and drying in sequence to obtain rod-shaped MoO3.
[0048] Figure 2 and Figure 3 The X-ray powder diffraction (XRD) pattern and scanning electron microscope (SEM) pattern of the rod-like MoO3 are shown respectively.
[0049] Furthermore, the volume ratio of concentrated nitric acid, isopropanol and deionized water is 1:(0.01-0.06):(2-5), and the mass fraction concentration of the above concentrated nitric acid is 69%.
[0050] Furthermore, in step S2, the temperature of the hydrothermal reaction is 160-220° C., and the time of the hydrothermal reaction is 12-36 hours.
[0051] In summary, the present invention provides a method for preparing a CoS2 / MoS2 rod-shaped material with surface-loaded particles by combining a solvothermal method, a room temperature stirring method and a hydrothermal vulcanization method. In the synthesis method, an appropriate amount of functional reagents are introduced during the solvothermal reaction process and the room temperature stirring process. For example, polyvinyl pyrrolidone (PVP) adjusts the viscosity of the mixed solvent during the room temperature stirring process, can be adsorbed on the surface of the MoO3 rod-shaped structure, improves the surface binding energy, and is beneficial to the CoS2 / MoS2 rod-shaped material. 2+ The uniform loading on the MoO3 surface and participation in the formation of the metal organic framework; the introduction of 2-methylimidazole and benzimidazole into the room temperature stirring process can effectively inhibit the trace hydrolysis of cobalt ions and play a ligand role to improve the yield and uniformity of the precursor.
[0052] In addition, different mixed solvent systems were involved in the solvothermal reaction process and the room temperature stirring process. For example, HNO3, H2O and isopropanol were used as mixed solvents in the solvothermal reaction. 24 Mo7N6O 24 The dissolution of 4H2O and the formation of MoO3 provide a suitable acidic and polar environment; methanol and propylene glycol as mixed solvents in the room temperature stirring process can not only dissolve cobalt salts and related reagents, but also improve the dispersibility and stability of the mixed system, provide a certain system viscosity, and are conducive to the functionalization of the surface of the MoO3 rod-like structure.
[0053] During the hydrothermal vulcanization process, thioacetamide provided a sulfur source, and regulated the surface nucleation sites and crystal vulcanization process under high temperature conditions, ultimately forming a CoS2 inorganic phase with granular dispersion on the surface, while the interior of the rod-like structure was a MoS2 phase structure with a high degree of crystallization.
[0054] Therefore, the reaction system, preparation process, vulcanization mechanism and microscopic morphology of the composite material of the present invention are greatly different from the MoO3 / Zn composite material in the prior art.
[0055] Example 2
[0056] On the basis of Example 1, the present invention provides a CoS2 / MoS2 composite material, which is prepared by the synthesis method of Example 1. The CoS2 / MoS2 composite material is rod-shaped MoS2 with surface-loaded particles, and the loaded particles are CoS2.
[0057] The synthesis method of the CoS2 / MoS2 composite material is briefly described as follows:
[0058] After mixing concentrated nitric acid, isopropanol and deionized water, add H 24 Mo7N6O 24 Rod-shaped MoO3 was obtained by solvothermal reaction of 4H2O.
[0059] The rod-shaped MoO3 is mixed with a mixture of methanol and glycerol, polyvinyl pyrrolidone and a soluble cobalt salt, and then 2-methylimidazole and benzimidazole are added, and after being stirred evenly at room temperature, the mixture is washed, dried and calcined to obtain a Co-Mo / C precursor;
[0060] The Co-Mo / C precursor is dispersed in deionized water, a sulfur source is added for hydrothermal vulcanization, and the obtained product is washed, dried and calcined to obtain a CoS2 / MoS2 composite material.
[0061] Furthermore, the diameter of the rod-shaped MoS2 is 0.1 to 1 μm, the aspect ratio is 10 to 30:1, and the particle size of the CoS2-loaded particles is 0.01 to 0.5 μm.
[0062] The technical solution of the present invention is described below by specific examples:
[0063] Example 3
[0064] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0065] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0066] S3. Add the obtained 0.5 g of rod-shaped MoO3 into a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of cobalt nitrate, stir evenly, and obtain solution A.
[0067] S4. Dissolve 1 g of 2-methylimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0068] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0069] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal vulcanization at 200° C. for 24 h.
[0070] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0071] Example 4
[0072] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0073] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0074] S3. Add the obtained 0.5 g of rod-shaped MoO3 into a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of cobalt nitrate, stir evenly, and obtain solution A.
[0075] S4. Dissolve 1 g of 2-methylimidazole and 0.05 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0076] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0077] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal vulcanization at 200° C. for 24 h.
[0078] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0079] Example 5
[0080] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0081] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0082] S3. Add the obtained 0.5 g of rod-shaped MoO3 into a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of cobalt nitrate, stir evenly, and obtain solution A.
[0083] S4. Dissolve 1 g of 2-methylimidazole and 0.05 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0084] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0085] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal vulcanization at 160° C. for 24 h.
[0086] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0087] Example 6
[0088] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0089] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0090] S3. Add 0.5 g of the obtained rod-shaped MoO3 to a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of cobalt chloride, stir evenly, and obtain solution A.
[0091] S4. Dissolve 1 g of 2-methylimidazole and 0.05 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0092] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0093] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal sulfurization at 200° C. for 24 hours to obtain a CoS2 / MoS2 precursor.
[0094] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0095] Example 7
[0096] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0097] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0098] S3. Add the obtained 0.5 g of rod-shaped MoO3 into a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of cobalt sulfate, stir evenly, and obtain solution A.
[0099] S4. Dissolve 1 g of 2-methylimidazole and 0.05 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0100] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0101] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal sulfurization at 200° C. for 24 hours to obtain a CoS2 / MoS2 precursor.
[0102] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0103] Example 8
[0104] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0105] S2. The mixed solution obtained in S1 is transferred to a reactor for hydrothermal crystallization reaction. After sealing, it is placed in a vacuum drying oven with the parameters set to 200°C and kept warm for 24 hours. Then, it is centrifuged, washed, and dried to obtain rod-shaped MoO3.
[0106] S3. Add 0.5 g of the obtained rod-shaped MoO3 to a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of Co(NO3)2·6H2O, stir evenly, and obtain solution A.
[0107] S4. Dissolve 0.5 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0108] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0109] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal sulfurization at 200° C. for 24 hours to obtain a CoS2 / MoS2 precursor.
[0110] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0111] Example 9
[0112] S1. Mix 10 mL of concentrated nitric acid, 50 mL of H2O, and 0.15 mL of isopropanol, then add 2 g of H 24 Mo7N6O 24 ·4H2O and stir evenly to obtain a mixed solution.
[0113] S2. Transfer the mixed solution obtained in S1 to a reactor for hydrothermal crystallization reaction, seal it and put it into a vacuum drying oven, set the parameters to 180°C, keep warm for 36 hours, then centrifuge, wash and dry to obtain rod-shaped MoO3.
[0114] S3. Add 0.5 g of the obtained rod-shaped MoO3 to a mixed solution of 50 mL of methanol and 0.5 mL of propylene glycol. After ultrasonication, add 0.25 g of PVP and 1.5 g of Co(NO3)2·6H2O, stir evenly, and obtain solution A.
[0115] S4. Dissolve 1 g of 2-methylimidazole and 0.05 g of benzimidazole in 20 mL of methanol and stir evenly to obtain solution B.
[0116] S5. Add solution B to solution A in S3, stir for 2 hours, wash, dry and calcine to obtain a Co-Mo / C precursor.
[0117] S6. Disperse the Co-Mo / C precursor in deionized water, add thioacetamide, stir evenly, and then perform hydrothermal sulfurization at 200° C. for 24 hours to obtain a CoS2 / MoS2 precursor.
[0118] S7. The product obtained in step S6 is centrifuged, washed, dried and calcined to finally obtain a rod-shaped MoS2 material loaded with CoS2 particles.
[0119] Example 10
[0120] The present invention also provides an application of the CoS2 / MoS2 composite material, which is used in the direct synthesis of low-carbon alcohols from synthesis gas, has excellent reaction activity and low-carbon alcohol selectivity, and has good application prospects.
[0121] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for synthesizing a CoS2 / MoS2 composite material, characterized in that: include: Add rod-shaped MoO3 to a mixture of methanol and propylene glycol, then add polyvinyl pyrrolidone and a soluble cobalt salt, and mix well to obtain solution A; Adding a solution B of 2-methylimidazole and benzimidazole into the solution A, stirring, washing, drying and calcining to obtain a Co-Mo / C precursor; The Co-Mo / C precursor is dispersed in deionized water, a sulfur source is added to carry out a hydrothermal sulfurization reaction, and the product is washed, dried and calcined to finally obtain the CoS2 / MoS2 composite material.
2. The synthesis method according to claim 1, characterized in that The preparation process of the rod-shaped MoO3 is as follows: Mix concentrated nitric acid, isopropanol and deionized water, then add H 24 Mo7N6O 24 ·4H2O is stirred evenly, and the obtained mixed solution is subjected to hydrothermal reaction, washing and drying in sequence to obtain the rod-shaped MoO3.
3. The synthesis method according to claim 1, characterized in that The molar ratio of the rod-shaped MoO3, the polyvinyl pyrrolidone, the soluble cobalt salt, the 2-methylimidazole and the benzimidazole is 1: (0.5-2): (0.05-0.25): (0-1.5): (0-0.1); The molar number of the polyvinyl pyrrolidone is calculated as a monomer, and the molar mass of the monomer is 111; The molecular weight of the polyvinyl pyrrolidone is less than 1 million.
4. The synthesis method according to claim 1, characterized in that The soluble cobalt salt is any one of cobalt nitrate, cobalt chloride and cobalt sulfate.
5. The synthesis method according to claim 1, characterized in that The stirring time of adding the solution B of 2-methylimidazole and benzimidazole into the solution A is 2 to 6 hours.
6. The synthesis method according to claim 1, characterized in that The temperature of the hydrothermal vulcanization reaction is 150-240° C., the heating rate is 1-3° C. / min, and the time of the hydrothermal vulcanization reaction is 12-36 hours.
7. The synthesis method according to claim 2, characterized in that The volume ratio of the concentrated nitric acid, the isopropanol and the deionized water is 1:(0.01-0.06):(2-5); the mass fraction concentration of the concentrated nitric acid is 69%; and / or, The temperature of the hydrothermal reaction is 160-220° C., and the time of the hydrothermal reaction is 12-36 hours.
8. A CoS2 / MoS2 composite material, characterized in that: The CoS2 / MoS2 composite material is a rod-shaped MoS2 with surface-loaded particles, and the loaded particles are CoS2; The synthesis method of the CoS2 / MoS2 composite material comprises: After mixing concentrated nitric acid, isopropanol and deionized water, add H 24 Mo7N6O 24 ·4H2O undergoes solvothermal reaction to obtain rod-shaped MoO3; The rod-shaped MoO3 is mixed with a mixture of methanol and glycerol, polyvinyl pyrrolidone, and a soluble cobalt salt, and then 2-methylimidazole and benzimidazole are added, and after stirring evenly at room temperature, the mixture is washed, dried, and calcined to obtain a Co-Mo / C precursor; The Co-Mo / C precursor is dispersed in deionized water, a sulfur source is added for hydrothermal vulcanization, and the product is washed, dried and calcined to obtain a CoS2 / MoS2 composite material.
9. The CoS2 / MoS2 composite material according to claim 9, characterized in that: The diameter of the rod-shaped MoS2 is 0.1 to 1 μm, and the aspect ratio is 10 to 30:1; The particle size of the loaded particles is 0.01-0.5 μm.
10. An application of a CoS2 / MoS2 composite material, characterized in that: The CoS2 / MoS2 composite material is used in the direct reaction of synthesis gas to synthesize low-carbon alcohols.
Citation Information
Patent Citations
Preparation method of monodisperse molybdenum trioxide solid microsphere
CN102874873A